Capital controls and financial crises - Aizenman, Joshua 1949- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1999)
The purpose of this paper is to explain the reluctance of developing countries to open up their capital market to foreigners, and the conditions inducing an emerging market economy to switch its policies. We consider an economy characterized initially by a one-sided openness to the capital market domestic agents can borrow internationally, but foreign agents cannot hold domestic equity. We identify conditions under which the emerging market's capitalists would oppose financial reform. This would be the case if 'green field' investment by multinationals would bid up real wages, reducing thereby the rents of domestic capitalists. A financial crisis that raises the domestic interest rate and causes a real exchange rate depreciation may induce the emerging market's capitalists to support opening up the economy to FDI. This attitude switch is more likely to occur the greater the debt overhang, the lower the borrowing constraint, and the weaker the market power of foreign entrepreneurs. Even in these circumstances, the emerging market's capitalists would prefer a partial reform to a comprehensive one -- they would prefer to maintain the restrictions on 'green field' FDI.